PENGALAMAN PERAWATAN IBU YANG MEMILIKI BAYI GIZI BURUK DI KABUPATEN REJANG LEBONG, BENGKULU: STUDI FENOMENOLOGI - Tonny C. Maigoda; Aswawarman Aswawarman; Sri Muljati (Persagi, 2009)
Caring Experiences of Mothers Who Have Malnourished Infants In Rejang Lebong District, Bengkulu Province: A Phenomenological Study).Background: Rejang Lebong District has the highest prevalence of malnourished under-fives among all districts of Bengkulu Province. Theoretically, to overcome malnutrition a good strategy of nutrition education to mothers and nurturing the children were really required. Therefore, the problem came out how mothers nurturing their malnourished children in Rejang Lebong District.Objectives: This research aims was to find out the experience of nursing malnourished children by mothers in Rejang Lebong Municipality.Methods: A qualitative approach was used to conduct this research by using Focus Group Discussion particularly phenomenology approach. In order to collect information 20 respondents were interviewed consisted of: 4 midwives, 3 community leaders, 6 village leaders, and 7 cadres.Results: The result showed that colostrums was not given to babies, because of dirty milk, children were not given breast milk cause of lack of breast milk mother. Moreover, children frequently was given snack which was not nutritious food. Other aspects were that people used drinking water from the river which was not good quality, moreover them others did not use soap to wash the dishes.Conclusions: Malnourished children frequently got sick accompanied by fever, diarrhea, cough, influenza, and to overcome these diseases the mothers brought their children to the health center and midwife, however, most of them cured by buying free medicine. The knowledge of mothers about the usage of colostrums, breast care, nutritious food, avoiding from infection diseases and nurturing their children still were not good enough.Keywords: malnourished infants, mothers' caring experiences, phenomenological study.